2018
DOI: 10.1159/000493268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strict Volume Control on Renal Progression and Mortality in Non-Dialysis-Dependent Chronic Kidney Disease Patients: A Prospective Interventional Study

Abstract: Objective: The aim of this study was to examine the effect of volume status on the progressions of renal disease in normovolemic and hypervolemic patients with advanced non-dialysis-dependent chronic kidney disease (CKD) who were apparently normovolemic in conventional physical exam­ination. Materials and Methods: This was a prospective interventional study performed in a group of stage 3–5 CKD patients followed up for 1 year. Three measurements were made for volume and renal status for every patient. The flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Faucon et al [18] found that extracellular fluid measured using a tracer dilution method was associated with progression to end-stage kidney disease and mortality in patients with stage 1-4 CKD. Strict volume control with use of diuretics showed a positive effect on progression of CKD and delayed initiation of RRT in advanced nondialysis CKD patients [19]. In our cohort, other parameters indicating fluid overload, such as blood pressure and plasma NT-pro-BNP, were significantly associated with OH and with progression of CKD, which confirms the robustness of the relationship between volume overload and progression.…”
Section: Discussionsupporting
confidence: 79%
“…Faucon et al [18] found that extracellular fluid measured using a tracer dilution method was associated with progression to end-stage kidney disease and mortality in patients with stage 1-4 CKD. Strict volume control with use of diuretics showed a positive effect on progression of CKD and delayed initiation of RRT in advanced nondialysis CKD patients [19]. In our cohort, other parameters indicating fluid overload, such as blood pressure and plasma NT-pro-BNP, were significantly associated with OH and with progression of CKD, which confirms the robustness of the relationship between volume overload and progression.…”
Section: Discussionsupporting
confidence: 79%
“…The most striking finding of the present study was that the GNRI was correlated with several major risk factors for accelerated CKD progression and CVD including DM, hypertension, eGFR, UPCR, and inflammatory markers [16,17]. Interestingly, we observed a significant and inverse relationship between the GNRI and overhydration, which has also been reported to be independently predictive of an increased risk of adverse renal and CV outcomes in nondialysis CKD patients [14,18]. The underlying mechanisms linking the nutritional status, overhydration, and proteinuria are not clear.…”
Section: Discussionsupporting
confidence: 63%
“…Kidney volume, as stated in various studies, can be a significant prognostic biomarker for risk assessment and disease tracking, as CKD patients usually develop fluid overload associated with systemic inflammation [ 36 ]. This volume overload has been linked to a decrease in renal function in advanced CKD patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%